2014
DOI: 10.3846/btp.2014.516
|View full text |Cite
|
Sign up to set email alerts
|

The Research of the Causal Relationship Between Unemployment and Emigration in Lithuania

Abstract: This paper aims to investigate the causal relationship between unemployment and emigration in Lithuania using Granger – causality test. The research is based on annual data spanning the period of 2004–2012. The investigation encompasses two steps. Firstly, the authors have analyzed the Lithuanian position regarding relationship between unemployment rate and emigration in the context of the European Union countries; secondly, the causality between unemployment and emigration has been determined in the case of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Meanwhile, the more students recognized that high unemployment pushes people abroad, the more they were likely to consider emigration as a possible outcome. The finding is consistent with the results from multiple studies that found high unemployment as one of the main causes of emigration from Lithuania [15,17,32]. Consistently, the proportion of students who intended to emigrate from Lithuania was smaller as compared to pharmacists, where more than one quarter expressed wishes to work in other EU countries in 2004 [25].…”
Section: Discussionsupporting
confidence: 82%
“…Meanwhile, the more students recognized that high unemployment pushes people abroad, the more they were likely to consider emigration as a possible outcome. The finding is consistent with the results from multiple studies that found high unemployment as one of the main causes of emigration from Lithuania [15,17,32]. Consistently, the proportion of students who intended to emigrate from Lithuania was smaller as compared to pharmacists, where more than one quarter expressed wishes to work in other EU countries in 2004 [25].…”
Section: Discussionsupporting
confidence: 82%
“…ANOVA p value will show if the hypothesis can be accepted and if statistically significant impact was found (significance level is 0,05). If the ANOVA p value is less than the significance level of 0,05, it means that statistically significant relation between dependent and independent variables exists (Dudzevičiūtė & Čekanauskas, 2014).…”
Section: H 2 : National Intellectual Capital Components Have Impact On Economic Growthmentioning
confidence: 99%
“…(IOM, 2004, p. 41) According to Divinský (2005), the Slovak expert on migration issues, "migration management" is a term which is hierarchically superior to the term "migration policy". In his understanding, the migration policy constitutes one of the three basic pillars of migration management; the others two being migration legislature and institutions acting in this field (Divinský, 2005;Bargerová & Divinský, 2008;Dudzeviciute & Cekanauskas, 2014;. It is obvious at the first sight that defining migration policy is not as easy as it seems.…”
Section: Definition Of the Migration Policymentioning
confidence: 95%